2015
DOI: 10.1002/ajmg.a.36921
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the phenotype of supernumerary marker chromosome 20 in a patient with syndromic pierre robin sequence: Combinatorial effect of gene dosage and uniparental disomy

Abstract: Clinical phenotypes in individuals with a supernumerary marker chromosome (SMC) are mainly caused by gene dosage effects due to the genes located on the SMC. An additional effect may result from uniparental disomy (UPD). Consequently, the occurrence of UPD may be a confounding factor in identifying genotype-phenotype correlations in SMC syndromes. Here, we report on a patient that illustrates this problem; the phenotype of this patient was a consequence of a combined effect of gene dosage and UPD. The proband … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Also, abnormal karyotypes were seen in 34 cases with the reported genetic mutations [Aboura et al, 2002;Ounap et al, 2005;Velagaleti et al, 2005;Gerth-Kahlert et al, 2011;Davidson et al, 2012;Fukami et al, 2012;Izumi et al, 2012aIzumi et al, , 2015Basart et al, 2015;Capkova et al, 2017;Schoner et al, 2017]. Although all the 39 studies had assessed the genetic mutations associated with PRS, a few critical limitations were observed: All the studies were heterogeneous, and only 5 cohort studies that met the inclusion criteria were available for data analysis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, abnormal karyotypes were seen in 34 cases with the reported genetic mutations [Aboura et al, 2002;Ounap et al, 2005;Velagaleti et al, 2005;Gerth-Kahlert et al, 2011;Davidson et al, 2012;Fukami et al, 2012;Izumi et al, 2012aIzumi et al, , 2015Basart et al, 2015;Capkova et al, 2017;Schoner et al, 2017]. Although all the 39 studies had assessed the genetic mutations associated with PRS, a few critical limitations were observed: All the studies were heterogeneous, and only 5 cohort studies that met the inclusion criteria were available for data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although genetic mutations were reported in most of the studies, only 21 studies had assessed genetic mutations in the proband's family members to demonstrate familial inheritance [Melkoniemi et al, 2003;Ounap et al, 2005;Johnston et al, 2010;Gerth-Kahlert et al, 2011;Gripp et al, 2011;Izumi et al, 2012aIzumi et al, , 2015Amarillo et al, 2013;Ehmke et al, 2014;Suemori et al, 2014;Bacrot et al, 2015;Castori et al, 2016;Kohmoto et al, 2016;Xu et al, 2016;Capkova et al, 2017;Powis et al, 2017;Schoner et al, 2017;Sleiman et al, 2017;Yang et al, 2017;Højland et al, 2018;Knapp et al, 2019]. Yang et al [2017] reported genetic mutations in 3 members from a family with manifestations of nsPRS, while the family members without any clinical signs of nsPRS did not exhibit genetic mutations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations